Implementation of Accrual Based Accounting in Improving Empowerment Small and Medium Enterprises (SMEs) District Rungkut Surabaya - Gideon Setyo Budiwitjaksono; Indrawati Yuhertiana (Nusantara Science and Technology Proceedings)
This article aims to explain the application of accrual accounting in the financial reporting presents creative industry businesses to better support decision making. The application of accrual accounting can provide important information for entrepreneurs. The information generated from the recording process can be used to analyze and measure performance as financial capabilities of a business, especially SMEs craftsman creative industries. Data collection using observation method and interview with the resource (entrepreneur) with cluster sample selection technique, involving 5 (five) persons in each representative of the business group from each region. The result shows that Understanding accrual basis system for business actor especially creative industry entrepreneurs in Surabaya Surabaya region requires gradual learning comprehension of recording system based on accrual for business actor need learning gradually and continuously. Through motivation, determination and hard work can be a key factor in the successful implementation of accrual-based accounting to realize community empowerment.